1989
DOI: 10.1172/jci114025
|View full text |Cite
|
Sign up to set email alerts
|

Role of mast cells in anaphylaxis. Evidence for the importance of mast cells in the cardiopulmonary alterations and death induced by anti-IgE in mice.

Abstract: We used genetically mast cell-deficient WBB6F,-W/WV and WCB6F1-S1/S1d mice and the congenic normal (+/+) mice to investigate the effects of intravenous infusion of goat antimouse IgE on heart rate (HR), pulmonary dynamic compliance (Cdyn), pulmonary conductance (GL), and survival. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 37 publications
5
60
0
Order By: Relevance
“…To investigate this hypothesis in greater detail we proceeded with the murine models. inflammatory events during an allergic reaction is an increase in vascular permeability (18,19). Mice were sensitized s.c. with anti-DNP IgE antibody and then challenged intravenously 24 hours later with DNP-HSA, IL-33, or IL-33ϩDNP-HSA, together with Evans blue.…”
Section: Il-33 Expression Is Increased In Patients Withmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate this hypothesis in greater detail we proceeded with the murine models. inflammatory events during an allergic reaction is an increase in vascular permeability (18,19). Mice were sensitized s.c. with anti-DNP IgE antibody and then challenged intravenously 24 hours later with DNP-HSA, IL-33, or IL-33ϩDNP-HSA, together with Evans blue.…”
Section: Il-33 Expression Is Increased In Patients Withmentioning
confidence: 99%
“…The clinical consequences of type I hypersensitivity triggered by mast cells can range from localized reactions including allergic rhinitis, asthma, atopic dermatitis and food allergies, to severe life-threatening systemic reactions such as anaphylaxis. Because mast cells are pivotal to allergic reactions and express a high density of ST2, and because recent reports showed that IL-33 can induce mast cells to produce proinflammatory cytokines in vitro (14)(15)(16)(17), we investigated the potential role of IL-33 in allergic SAS in humans and in murine models of IgE-mediated passive cutaneous anaphylaxis (PCA) and passive systemic anaphylaxis (PSA), the most commonly used models to study specific mast cell responses in vivo (18)(19)(20).…”
mentioning
confidence: 99%
“…The crosslinking of antigen to IgE on the surface of mast cells is believed to provide the stimulus for mast cell degranulation in early-phase allergic reactions, an event that precipitates a cascade of inflammatory events in response to allergen (Martin et al, 1989(Martin et al, , 1993Oshiba et al, 1996). Patients allergic to Dermatophagoides pteronyssinus (Der p1) and exposed to synthetic peptides derived from the allergen Der p1 were shown to have activated platelets.…”
Section: Platelet Involvement In Antigen Recognitionmentioning
confidence: 99%
“…The most comprehensively described mechanism of anaphylaxis involves the crosslinking of IgE bound to Fc RI on mast cells, leading to the release of preformed mediators, such as histamine, heparin, and tryptase; lipid-derived mediators, such as prostaglandins, leukotrienes, and platelet-activating factor; and cytokines. Collectively, these mediators initiate rapid vascular permeability, leading to plasma extravasation, tissue edema, bronchoconstriction, mucous overproduction, and leukocyte recruitment (13,14). In rodents, mast cell degranulation, temperature loss, and mortality associated with active systemic anaphylaxis can also be mediated through the crosslinking of IgG1 bound to Fc␥RIII (15,16).…”
mentioning
confidence: 99%